Policy and blame attribution: citizens’ preferences, policy reputations, and policy surprises - Sulitzeanu-Kenan, Raanan; Zohlnhöfer, Reimut (Political behavior, 2019)
Negativity bias suggests that the attribution of blame to governments, for alleged or actual policy failures, is disproportionately pertinent for their popularity. However, when citizens attribute blame for adverse consequences of a policy, does it make a difference which policy was it, and who was the political agent that adopted the policy? We posit that the level of blame citizens attribute to political agents for policy failures depends on three policy-oriented considerations: (1) the distance between a citizen’s ideal policy and the agent’s established policy position; (2) the distance between a citizen’s ideal policy and the agent’s concrete policy choice; and (3) the distance between the agent’s established policy position and her concrete policy choice. The inherent relationship between these three policy-oriented considerations renders their integration in one model a theoretical and methodological imperative. The model provides novel observable predictions regarding the conditions under which each of the three policy-oriented factors will produce either pronounced or subtle observable effects on blame attribution. We test the model’s predictions in two survey experiments, in Israel and in Germany. The results of both experiments are highly consistent with the model’s predictions. These finding offer an important contribution by specifying the ways in which individual-level preferences interact with politicians’ policy reputations and policy choices to shape blame attribution. Our model entails unintuitive revisions to several strands of the literature, and in the “Discussion” section we provide tentative support for the applicability of this model to other political judgments beyond blame attribution.